A taxonomic reappraisal of the Smooth Slug Snake Asthenodipsas laevis (Boie, 1827) (Squamata: Pareidae) in Borneo with the description of two new species - Quah, Evan S.h.; Grismer, L. Lee; Lim, Kelvin K.p.; Anuar, M.s. Shahrul; Imbun, Aul Y. (Zootaxa, 2019)
A review of the taxonomic status of the Smooth Slug Snake (Asthenodipsas laevis) in Borneo resulted in the discovery of two previously unrecognised species from the highlands of Sabah, East Malaysia. Asthenodipsas jamilinaisi sp. nov. and A. stuebingi sp. nov. are presumed to be closely related to A. laevis based on similarities in pholidosis and patterning but can be separated from A. laevis by their dorsal scale rows of 15/15/15 vs 15/15/13 and the presence of a sharp vertebral keel. Asthenodipsas jamilinaisi sp. nov. can be further differentiated from A. stuebingi sp. nov. by the greatly enlarged size of the vertebral scales, higher number of ventrals in males (173–175 vs 165), higher number of subcaudals (53 vs 35–47) and colour pattern (dark overall with indistinct bands vs lighter head and body with clear, distinct bands and a dark neck patch). The discovery highlights the need for more careful examination of much of the herpetofauna of Borneo that still remains underestimated and understudied. There is an urgent need for continued surveys into its diversity and the collection of genetic material for integrated taxonomic revisions.